2013
DOI: 10.1007/s10661-013-3581-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fomesafen on soil enzyme activity, microbial population, and bacterial community composition

Abstract: Fomesafen is a diphenyl ether herbicide that has an important role in the removal of broadleaf weeds in bean and fruit tree fields. However, very little information is known about the effects of this herbicide on soil microbial community structure and activities. In the present study, laboratory experiments were conducted to examine the effects of different concentrations of fomesafen (0, 10, 100, and 500 μg/kg) on microbial community structure and activities during an exposure period of 60 days, using soil en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…DGGE profiling of soil community DNA fragments enables to monitor the spatial and temporal changes in microbial community structure and provides a comparative picture of the dominant microbial species of polluted soils (Qu et al 2011;Zhang et al 2014). Phylogenetic analysis of 16S rRNA gene clearly indicated the selection in eubacterial community structure with response to IWE pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGGE profiling of soil community DNA fragments enables to monitor the spatial and temporal changes in microbial community structure and provides a comparative picture of the dominant microbial species of polluted soils (Qu et al 2011;Zhang et al 2014). Phylogenetic analysis of 16S rRNA gene clearly indicated the selection in eubacterial community structure with response to IWE pollution.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the higher percentage of Proteobacteria, Firmicutes, and Actinobacteria were noticed in long-term polluted soils in which hydrocarbon was the main contaminant (Vivas et al 2008). Pollution-induced bacterial community shifts were observed with organic pollutants such as phenanthrene, fluoranthene, pyrene, benzo(a)pyrene, and herbicides (Tian et al 2008;Zhang et al 2014). Studies suggested that the indigenous bacteria are very sensitive to contaminants and respond rapidly to organic pollutants (Tian et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…The plate counting method [13] was applied to measure soil microbial numbers on selective media. Luria-Bertani (LB) medium was used to culture bacterial colonies.…”
Section: Determining Soil Microbial Populationmentioning
confidence: 99%
“…Many reports showed that insecticides also can alter ecosystems through concentrating along food chain (Stephenson et al 2006). Insecticides are often found in crop, food, soils, and water, and the large amount of insecticide application often leads to insecticide residues in soils, which can affect the soil microbial community by changing their number, microbial activity, and diversity (Zhang et al 2010(Zhang et al , 2014Zabaloy et al 2012;Cycon et al 2013;Cai et al 2015a).…”
Section: Introductionmentioning
confidence: 99%